NUMERICAL SCHEME FOR BACKWARD DOUBLY STOCHASTIC DIFFERENTIAL EQUATIONS WITH TIME DELAYED COEFFICIENTS (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we present some assumptions to get the numerical scheme for backward doubly stochastic dierential delay equations (shortly-BDSDDEs), and we propose a scheme of BDSDDEs and discuss the numerical convergence and rate of convergence of our scheme.